Namibia Identity Management : System Analysis - World Bank Group (World Bank, Washington, DC, 2016)
Namibia should be congratulated on their forward looking and energetic public sector because of the strategic vision of the leadership, as could be observed in the Ministry of Home Affairs and Immigration (MHAI). MHAI is responsible for the technical and organizational infrastructureused to define, design, and administer the identity management system in Namibia.And from what could be observed there are systems and procedures in place to administer the registration of births and deaths and the linkage with the Namibian identification card. A complicating factor is the continued use of South West African (SWA) identity cards and the legacy register these represent. The fact that these have yet to be phased out represents both an administrative challenge which can delay identity verification processes, but also a security risk in that the issuance of the cards were based on standards that are different from today’s requirements for strong verification and authentication practices. The digital connectivity is a prerequisite for the interoperability of databases for the purpose of efficient deployment and use of electronic identification cards, and as such is a cornerstone of an identity management system. Namibia appears to be in a transitional phase with respect to putting in place the infrastructure needed for making their electronic governance vision a reality.Introducing an e-ID card has the potential to increase the effectiveness of both the public and the private sectors, and improve service delivery to citizens and residents alike. The proposal to Namibia is to consider a multi-stepapproach to identification cards by phasing out the SWA and the current national identity card, while phasing in an electronic identification card.A number of policy decisions are necessary to establish a legal, institutional and technical basis for a digitally integrated identity management system for Namibia. Namibia has already advanced with respect to defining thefoundations for linking services and systems, as well as thinking ahead with respect to the development and implementation of the same.